Feasibility study on potential Jatropha plantation using GIS technique / Norshahirah Md Akhir - Md Akhir, Norshahirah (2020)
Jatropha has been identified as the most suitable oil seed-bearing plant for an alternative biodiesel source due to its various favourable attributes like favourable climate conditions, short gestation period, high oil recovery and quality of the oil. Although it has been introduced in the year 2012, the implementation was unsuccessful because lack to find suitable place but, with latest technologies for precision farming, Geographic Information System (GIS) technique can help on deciding suitable area for Jatropha plantation. Therefore, the objective of this study are to i) determine significant weightage of parameters for Jatropha plantation and ii) identify the suitable location Jatropha plantation. The study area is carried out at peninsular Malaysia and five (5) variables such as rainfall, temperature, elevation, soil and land-use data were used to achieve the analysis. The analytical hierarchy process (AHP), in the combination of Geographical Information System (GIS) methods, was applied to compute the weightage of the selected criteria, which is in geospatial data types. A map of the potential Jatropha location was generated using the criteria weightage. This study can help the cultivation of jatropha in suitable areas and may reduce the burden on fossil fuels. It can assist smallholder-based initiatives to promote Jatropha cultivation on farmer-owned to enhance their living circumstances.